Mad heart be brave : essays on the poetry of Agha Shahid Ali - Ali, Kazim (Ann Arbor: University of Michigan Press, 2017)
"Agha Shahid Ali (1949-2001) published seven highly acclaimed poetry collections in his lifetime. A native of Kashmir, he was respected and beloved both in India and the United States, where he taught for two decades in writing programs at schools such as the University of Massachusetts-Amherst, the University of Utah, New York University, and Brooklyn College. Ali embraced traditional forms of Western poetry, such as the sonnet, pantoum, villanelle, Sapphic stanzas, and sestine, before innovating an approach in English to the traditional Urdu ghazal. His poetry won the praise of contemporary American masters of form like Carolyn Kizer, James Merrill, and Anthony Hacht and of poetic innovators like Michael Palmer and Donald Revell. Collectively, the twenty essays of Mad Heart Be Brave--some of which are by his former students, now highly regarded poets themselves--offer a comprehensive consideration of Ali's work as poet, teacher, translator, and thinker.There are essays that look at his embrace of traditional forms, his use of appropriation and palimpsest in his poetry, his work as a translator, his influence and approaches as a teacher, and his relationship to the poetry scenes in both India and the United States. Several pieces explore Ali's relationship to the Kashmiri conflict, the question of nationalism, and his groundbreaking collection, The Country Without a Post Office. Later essays look at the erotic content of his work as well as his innovation in poetic forms, including his work at bringing "real ghazals" (as he called them) into English. The book concludes with a retrospective piece by Amitav Ghosh and a comprehensive bibliography of Ali's published work that will be a major resource for future scholarship."--Page 4 of cover.
Introduction / Kazim Ali -- The world is full of paper : write to me / Sejal Shah -- Between postindependence and the Cold War : Agha Shahid Ali's publications with the Calcutta Writers Workshop / Rita Banerjee -- "This is an archive" : Agha Shahid Ali's postcards from Kashmir / Amanda Golden -- The veiled sweets : Agha Shahid Ali's surprising use of humor / Ravi Shankar -- Beyond borders, nations, and exclusivist identities : Agha Shahid Ali's poetics of plurality / Abin Chakraborty -- "Separation's geography" : Agha Shahid Ali's scholarship of evanescence / Amy Newman -- "A route of evanescence" : Agha Shahid Ali in America / Christopher Merrill -- The loved one always leaves : the poetic friendship of Agha Shahid Ali and James Merrill / Jason Schneiderman -- Agha Shahid Ali, world literature, and the representation of Kashmir / Stephen Burt -- The shifting nationalisms of Agha Shahid Ali's poetry / Raza Ali Hasan -- Missing home, imagining violence : Agha Shahid Ali's engagement with Kashmir / Syed Humayoun -- Poet in Srinagar / Feroz Rather -- Requiem : Agha Shahid Ali's last canzone / Dur E Aziz Amna -- Palimpsetic intertextualities in "A lost memory of Delhi" and "The last saffron" / Mihaela Moscaliuc -- Borrowed words : the use of quotations and italics in the ghazals of Agha Shahid Ali / Reginald Dwayne Betts -- "The grief of broken flesh" : the dialectic of desire and death in Agha Shahid Ali's lyrics / Mahwash Shoaib -- "Who will inherit the last night of the past?" : Agha Shahid Ali's architecture of nostalgia as translation / Shadab Zeest Hashmi -- The chain / Grace Schulman -- The postcard and the puzzle : for Agha Shahid Ali / Ada Limón -- The ghat of the only world : Agha Shahid Ali in Brooklyn / Amitav Ghosh -- An introduction to The beloved witness project and a selected bibliography of Agha Shahid Ali's publications in India and America, 1972-2001 / Patricia O'Neill with Reid Larson.
Includes bibliographical references.
Keywords: Agha, Shahid Ali; Agha, Shahid Ali, -- 1949-2001.; Ghazals -- History and criticism; Ghazals; Criticism, interpretation, etc